WAI-ARIA live regions and channels: ReefChat as a case example. - Thiessen P; Russell E (Disability & Rehabilitation: Assistive Technology, 2009)
Web 2.0, enabled by the AJAX architecture, has given rise to new levels of user interaction with web pages. Many of these new and extremely popular Web 2.0 pages are better classified as fully-fledged applications, some examples being Google Maps, Google Docs and Flickr. Unfortunately, accessibility support in most AJAX applications is lacking. The Web Accessibility Initiative - Accessible Rich Internet Applications markup presents a solution to making these applications accessible. This article will look at current ARIA documentation available for Web 2.0 developers, a new innovation involving channels, and present a real life example of an ARIA based solution involving an accessible AJAX chat, ReefChat, and an ARIA compatible screen reader, Fire Vox.